Gender bias in autism screening: measurement invariance of different model frameworks of the Autism Spectrum Quotient - Hannah L. Belcher; Nora Uglik-Marucha; Silia Vitoratou; Ruth M. Ford; Sharon Morein-Zamir (BJPsych Open, 2023)
Background The Autism Spectrum Quotient is a popular autism screening tool recommended for identifying potential cases of autism. However, many women with autism demonstrate a different presentation of traits to those currently captured by screening measures and assessment methods, such as the Autism Spectrum Quotient.